Pendampingan Learning Organization dalam Membentuk Kepemimpinan Unggul di SMK Darussalam 2 Pamulang - Haerudin, Muhamad; Yuanita, Dyta; Wulandari; Salam, Badru; Adawiyah, Rabiatul; Ramadhan, Daffa; Zubaidah, Siti; Pujilestari, Yulita; Siswandi, R Dede (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service research aims to implement and analyze the effectiveness of learning organization mentoring in fostering exemplary leadership at SMK Darussalam 2 Pamulang. The rationale for this initiative stems from the importance of strengthening educational leadership capacity that is adaptable to change, as well as the need to develop a learning organization culture within the school environment. The method used was a participatory approach through socialization activities, discussions, simulations, and practice-based mentoring over the three-day duration of the activity. The results of the activity showed a significant increase in participants’ understanding of the concept of a learning organization, as well as an improvement in leadership skills in facilitating learning and collaboration. Additionally, this activity also contributed to the formation of a more open, reflective, and collaborative organizational culture. Students also demonstrated increased participation in the learning process, reflecting the successful implementation of the learning organization model within the school environment. Thus, this mentoring program has proven effective in enhancing the quality of educational leadership and strengthening the culture of a learning organization. This initiative can serve as a relevant model for community service in the development of adaptive, innovative, and sustainable educational organizations.